Cellular repair factors influencing radiocurability of human malignant tumours. - Weichselbaum, R. R. (Nature Publishing Group, 1982)
We have studied the repair of X-ray-induced, potentially lethal damage (PLD) in 9 human tumour lines derived from tumours of varying radiocurability. Cells derived from 3 tumours considered non-radiocurable (1 osteosarcoma, 2 melanoma) repaired significantly more X-ray PLD than cells from 3 tumours considered radiocurable (2 breast, 1 neuroblastoma). The remaining tumour lines were intermediate in their ability for repair, and included cells from another osteosarcoma, a hypernephroma and a glioblastoma. We conclude that the repair of X-ray PLD may be an important cellular determinant of clinical radiocurability.